2011
DOI: 10.1096/fj.11-182741
|View full text |Cite
|
Sign up to set email alerts
|

A redox switch in C‐reactive protein modulates activation of endothelial cells

Abstract: C-reactive protein (CRP) has been implicated in the regulation of inflammation underlying coronary artery disease; however, little is known about the molecular mechanisms responsible for the expression of its pro- or anti-inflammatory activities. Here, we have identified the intrasubunit disulfide bond as a conserved switch that controls the structure and functions of CRP. Conformational rearrangement in human pentameric CRP to monomeric CRP (mCRP) is the prerequisite for this switch to be activated by reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 42 publications
2
92
0
3
Order By: Relevance
“…This has led us to propose that the dissociation of the CRP molecule is an activating mechanism that is required for the expression of enhanced bioactivities and is also a buffering mechanism that localizes the actions of mCRP into inflammatory loci to prevent the possible global effects directly induced by large-scale alterations in the serum levels of CRP [73]. Consistent with our proposal, immunohistochemical analyses using highly specific antibodies revealed that mCRP, not CRP, was the major isoform present in local lesions, including atherosclerotic plaques [55,76], diabetic kidneys [77] and stroke neovessels [78].…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiessupporting
confidence: 79%
See 4 more Smart Citations
“…This has led us to propose that the dissociation of the CRP molecule is an activating mechanism that is required for the expression of enhanced bioactivities and is also a buffering mechanism that localizes the actions of mCRP into inflammatory loci to prevent the possible global effects directly induced by large-scale alterations in the serum levels of CRP [73]. Consistent with our proposal, immunohistochemical analyses using highly specific antibodies revealed that mCRP, not CRP, was the major isoform present in local lesions, including atherosclerotic plaques [55,76], diabetic kidneys [77] and stroke neovessels [78].…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiessupporting
confidence: 79%
“…Comparable results were obtained with Cys-mutated mCRP, in which the two cysteines were mutated to alanines. These findings thus indicate the intra-subunit disulfide bond as an important switch modulating the activities of mCRP [55].…”
Section: Redox Regulation Of Bioactivities Of Monomeric Crpmentioning
confidence: 65%
See 3 more Smart Citations